Clinical and histopathological characteristics of peruvian children with craniopharyngioma - Virú-Loza , Manuel André (2023)
Introduction: Craniopharyngiomas are benign tumors, of which up to 50% occur in children. However, there are no studies in Peruvian children. Objective: to describe the clinical and histopathological characteristics of children with craniopharyngioma hospitalized at the Edgardo Rebagliati Martins National Hospital between August 2019 and May 2021. The study: The design is cross-sectional and the data source were medical records. Information on sex, age, surgeries and characteristics related to the first tumor resection surgery were collected. Findings: We included 12 patients. 83.3% were male, at the time of diagnosis the median age was 6 years and visual symptoms predominated, all had hormonal deficiencies after the first resection surgery. Conclusions: three received radiotherapy, one developed malignant transformation and one died. Future prospective studies are necessary.